Pengaruh Model Pelatihan Jarah Jauh .... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT This research was aimed to examine the influence of training toward knowledge, attitude and skill of Acute Respiratory Infections (ARI) case management for health care providers in Primary Health Care between those who obtained distance training model and classical model. This is a quasi-experimental study that was using non-randomised control group pretest-post test design. The subject of this research was health care providers in Primary Health Care that consists of nurses and midwifes including midwifes in villages. The number of the subjects was 62 people who work in 7 Primary Health Care in Karanganyar regency. The location of Primary Health Care and grouping training method was determined randomly. Research sample unit was determined by purposive sampling technique that based on determined characteristic. Characteristic of subject, variable of knowledge, attitude and skill in two groups before given treatment was in comparable initial condition. Analysis that used to measure the influence of treatment was done by t-test with confidence rate of p=0,05. The result of this research showed that: (1) there was improvement of knowledge, attitude and skill regarding Acute Respiratory Infections case management for health care provider in Primary Health Care between those who obtained long distance training model and classical model